Comparative genomics between Trichomonas tenax and Trichomonas vaginalis: CAZymes and candidate virulence factors - Mpeyako, Lenshina A.; Hart, Adam J.; Bailey, Nicholas P.; Carlton, Jane M.; Henrissat, Bernard; Sullivan, Steven A.; Hirt, Robert P. (Frontiers in Microbiology, 2024)
The oral trichomonad Trichomonas tenax is increasingly appreciated as a likely contributor to periodontitis, a chronic inflammatory disease induced by dysbiotic microbiota, in humans and domestic animals and is strongly associated with its worst prognosis. Our current understanding of the molecular basis of T. tenax interactions with host cells and the microbiota of the oral cavity are still rather limited. One laboratory strain of T. tenax (Hs-4:NIH/ATCC 30207) can be grown axenically and two draft genome assemblies have been published for that strain, although the structural and functional annotation of these genomes is not available. Methods: GenSAS and Galaxy were used to annotate two publicly available draft genomes for T. tenax, with a focus on protein-coding genes. A custom pipeline was used to annotate the CAZymes for T. tenax and the human sexually transmitted parasite Trichomonas vaginalis, the most wellcharacterized trichomonad. A combination of bioinformatics analyses was used to screen for homologues of T. vaginalis virulence and colonisation factors within the T. tenax annotated proteins. Results: Our annotation of the two T. tenax draft genome sequences and their comparison with T. vaginalis proteins provide evidence for several candidate virulence factors. These include candidate surface proteins, secreted proteins and enzymes mediating potential interactions with host cells and/or members of the oral microbiota. The CAZymes annotation identified a broad range of glycoside hydrolase (GH) families, with the majority of these being shared between the two Trichomonas species. Discussion: The presence of candidate T. tenax virulence genes supports the hypothesis that this species is associated with periodontitis through direct and indirect mechanisms. Notably, several GH proteins could represent potential new virulence factors for both Trichomonas species. These data support a model where T. tenax interactions with host cells and members of the oral microbiota could synergistically contribute to the damaging inflammation characteristic of periodontitis, supporting a causal link between T. tenax and periodontitis.